The Correlation Between English Education Study Program Students’ Strategies in Learning English Pronunciation and Their Achievement in Speaking - Assyfa Rahma Selvia Phita Loka; Imranuddin Imranuddin; Ildi Kurniawan (Yayasan Karinosseff Muda Indonesia, 2020)
The aim of this research was to identify students’ pronunciation learning strategies and speaking achievement among students of the English Study Program at Universitas Bengkulu. Then, the research would like to find out whether or not there was any significant correlation between both variables. The research was a correlational research. The population consisted of 79 students of the English Education Study Program at Universitas Bengkulu in academic year 2018/2019. The total sample included 79 students. The instruments were pronunciation learning strategies questionnaire and students’ score in speaking for presentation course from the lecturer. The collected data were analyed by Pearson Product Moment formula. The result of this research showed that the Social Strategy was the most frequently used with a mean score 3.9 (“often” category). Then, high achievement students and middle achievement students used all strategies. The means of strategy score for high acchievement students was 3.9 and the middle achievement students was 2.98. The result of this research also revealed that there was a correlation between students’ pronunciation learning strategies and speaking achievement besause the correlation coefficient was 0.595, in “moderate” correlation category. It is concluded that it is needed to strength students’ achievement through introducing pronunciation learning strategies deeply.